2012
DOI: 10.2337/dc11-2142
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator–Activated Receptor γ Polymorphism Pro12Ala Is Associated With Nephropathy in Type 2 Diabetes

Abstract: OBJECTIVEInsulin resistance plays a part in diabetic nephropathy (DN). The association between the peroxisome proliferator–activated receptor γ Pro to Ala alteration at codon 12 (Pro12Ala) polymorphism and the risk of insulin resistance has been confirmed. The association between the polymorphism and DN risk has also been widely studied recently, but no consensus was available up to now.RESEARCH DESIGN AND METHODSA systematic search of electronic databases (MEDLINE, Embase, and China National Knowledge Infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
(39 reference statements)
2
29
2
1
Order By: Relevance
“…These results highly suggest a protective functional role of PPARγ in diabetic nephropathy. In agreement with this conclusion, numerous studies containing a meta-analysis of 18 studies involving 3,361 patients convincingly demonstrated a significant protective effect against for T2DN [38]. And their results indicated rs1801282 C>G polymorphism was associated with the reduced risk of T2DN in Caucasians but no similar association was observed in Asians, but our study have found that the C>G polymorphism in rs1801282 showed a significant protective role for T2DN in both Asians and Caucasians.…”
Section: Discussionsupporting
confidence: 91%
“…These results highly suggest a protective functional role of PPARγ in diabetic nephropathy. In agreement with this conclusion, numerous studies containing a meta-analysis of 18 studies involving 3,361 patients convincingly demonstrated a significant protective effect against for T2DN [38]. And their results indicated rs1801282 C>G polymorphism was associated with the reduced risk of T2DN in Caucasians but no similar association was observed in Asians, but our study have found that the C>G polymorphism in rs1801282 showed a significant protective role for T2DN in both Asians and Caucasians.…”
Section: Discussionsupporting
confidence: 91%
“…18 publications addressing the association between PPARγ2 Pro12Ala polymorphism and DN risk were preliminarily eligible [8,9,17-30]. Table 1 presents the main characteristics of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…The most common gene polymorphism in human PPARγ2 gene is cytosine-guanine exchange in exon B (codon12) which results proline to alanine (Pro12Ala) substitution in the protein [6].The Pro12Ala polymorphism was first identified by Yen et al [7] in 1997 and regarded to reduce transcriptional activity of PPARγ2 [8], resulting in lower transcription levels of target genes [9],including tumor necrosis factor α ( TNF α ), leptin, resistin, adiponectin, and plasminogen activator in hibitor-1( PAI - 1 ), which play important roles in the process of inflammation and atherosclerosis. There are evidences that the resulting mutant transcription factor profoundly affects the energy metabolism and energy balance and is associated with the risks of atherogenesis [10][12] and diabetes [13], [14]. In addition, the Pro12Ala polymorphism was regarded to change the response of synthetic PPARγ agonists– thiazolidinediones (TZDs) treatment [15], which seemed to improve the insulin resistance [16] and limit atherosclerosis development [17].…”
Section: Introductionmentioning
confidence: 99%